The Impact of Shared Values on Psychological Empowerment - Shamah, Rania A. M.; Elsawaby, Shaymaa M. M.; Aboul-Ela, Ghadeer M. B. (Prabandhan: Indian Journal of Management, 2013)
Purpose: This research aims to examine and understand the level ofÂ Â Â psychological empowerment inside Egyptian organizations, namely the automobile industry; look at the impact of shared values on psychological empowerment; and investigate if there is a difference in the level of psychological empowerment held between females and males. Design/methodology/approach: The research study is an empirical research whereby the hypotheses were tested on the automobile distributor companies in Egypt. Questionnaires were used to collect the research data. Findings: The research results revealed a positive relationship between shared values and psychological empowerment. No significant difference was found between females and males with respect to the level of psychological empowerment they possessed. Research limitations/implications: The research questionnaires were distributed among the automobile companies located in Cairo and Giza governorates. Originality/value: Limited empirical research studies have examined the impact of shared values on psychological empowerment. Practitioners and researchers should find value in this unique research study.